Desenvolvimento de um sistema foto-oxidativo visando aplicação no tratamento de águas produzidas em campos de petróleo - Mota, André Luís Novais (2010)
Increasing concern with the environment, in addition to strict laws, has induced the industries to find alternatives to the treatment of their wastes. Actually, the oil industry has sought solutions to overcome a big environmental problem, i.e., oil field produced water being discharged to the sea. These effluents have organic compounds dissolved, such as polycyclic aromatic hydrocarbons, phenols, benzene, toluene, ethylbenzene and xylenes (BTEX). These compounds are difficult to be removed and have high toxicity. The advanced oxidation processes - AOP are effective to degradation of these organic compounds, because they generate hydroxyl radicals with high potential of oxidation. This work includes the reactor photochemical development applied in the photodegradation treatment (by photo-Fenton process) of wastewaters containing organic compounds dissolved, aiming at treatment and recovery the oil field produced water. The studied reactor allowed the evaluation of two ultraviolet radiation sources that is the main factor to describe the feasibility of the photo- Fenton treatment, i.e., sun and black light fluorescent lamps, and other relevant variables the process: concentration of reagents, irradiated area and also various reactor configurations to maximize the use of radiation. The organic matter degradation was verified with samples collected during the experimental and analyzed with a total organic carbon analyzer (TOC), which expressed the results in terms of mgC/L. The solar radiation was more effective than radiation from the lamps. It's an important factor for the operation costs cutting. Preliminary experiments applied to oil field produced water treatment have showed satisfactory results, reducing up to 76 % of organic matter